Mass Balance to the Production of Polyhydroxyalkanoates from Mixed Microbial cultures with Fruit Pulp - Bello, João Coelho Capela Guimarães (2019)
Bioplastics, specially polyhydroxyalkanoates(PHA), represent one of the best alterna tives to plastics from non-renewable sources. The production of PHA, from mixed micro bial cultures with low-cost feedstocks, as in this dissertation fruit pulp requires a process of three stages: treatment of the residues through anaerobic digestion which is used to feed both the selection and accumulation reactor. The biomass PHA-accumulating selec tion reactor is carried out on a feast and famine regime with uncoupled feeding from nitro gen an carbon, leading to increased selective pressure, where a ratio of COD:N:P(100:6.5:1:) is applied. The accumulation reactor is carried out on a fed-batch, and is inoculated from the sequential batch reactor and therefore is capable of accumulating PHA. All of the processes were followed along two months of operation, from the Up-flow Anaerobic Sludge Blanket Reactor to the accumulation stage. In the first and second reactors, no alterations were made, and they were just monitored to study its evolution. In the accumulation reactor, 9 batches were made with and without nutrients, to opti mize the process productivity. The following ratios were applied COD:N:P (100:6.5:1; 100:3,25:0.5;100:0:), to induce just little growth they were applied only in the first pulse. To understand how much fruit pulp is needed to produce 1 kg of PHA, mass balance study’s were made, to describe the general productivity of the process. The mass balance was made, while the acidogenic reactor had a high OLR, 16.09± gCODL−1d −1, and a conversion rate of 77%, it was considered to be the normal value of the operation. To the accumulation reactor, an average of every two batches where the same conditions were applied was used. Concluding that to produce 1kg of biopolymer from fruit pulp, the following quantities are needed: ACC-3/4 = 8011.6 gCOD; ACC(Nutri)-6/7 = 6906.8 gCOD, ACC(Nutri)-8/9 = 6142.6 gCOD.